The The Phohibition of Usury and its Implications for the Economy: A Study of Surah Al-Baqarah Verses 275-276 - Baharuddin, Nur Alisa; Abubakar, Achmad; Basri, Halimah (ADL ISLAMIC ECONOMIC : Jurnal Kajian Ekonomi Islam, 2023)
Usury is an important topic in the study of Islamic economics. The practice of usury that have existed since the days of Jahiliyah even long before and still exist today. The legal basis for the prohibition of usury explicitly and clearly described in QS. al-Baqarah/2:275-276. The purpose of this study is to determine the form of the prohibition of usury as described in the Qur’an and its implications for the community’s economy. This research uses qualitative research with library reseacrh method as a method to collect various relevant data with tafsir tahlili data analysis technique. The results show that the prohibition of usury has gone through several long legal stages until it is determined as a forbidden act. Usury, interest and buying and selling each have their own meaning and cannot be equated. Allah will forgive the sin of the usurer as long as he truly repents and leaves the act. Usury has implications for various sectors of human life, especially in the economic sector such as not increasing wealth, econommic inequality, a form of family economic colonization, disconnection of the productive economic sector (trande, industry and companies) and the emergence of inflation.